EUROPEAN UNION’S COMMITMENT TO FIGHT AGAINST THE HUMAN BEINGS TRAFFICKING, THE MODERN FORM OF SLAVERY - Laura-Cristiana SPĂTARU-NEGURĂ (Challenges of the Knowledge Society)
One of the most serious threats to the European Union is the organised crime. The EU is continuously adapting its response in order to best respond to the situation. Among different types of organised crime, human beings trafficking is one of the most seriously crimes worldwide, representing also a gross violation of human rights. Very often behind the human beings trafficking is the organised crime because is one of the most profitable criminal activities in the world. The numbers are very scary because it is estimated that the trafficked people to or within the EU are reaching several hundred thousands a year. The present study is intending to discover how the European Union intends to fight against the human beings trafficking, since there is a need to have a coherent action at the European level because of the criminals can easily operate across border.